A new diatom (Surirellaceae: Bacillariophyta) species—Surirella caljoniana sp. nov.—in Göydün Spring, Sivas in Eastern Anatolia, Republic of Türkiye - SOLAK, CÜNEYT NADIR; COCQUYT, CHRISTINE; HAMILTON, PAUL B.; HOLMES, JOE; YILMAZ, ELIF; KESBIÇ, IŞIL (Magnolia Press, 2023)
A new species Surirella caljoniana sp. nov. is described from a unique microenvironment in the mountainous region of Türkiye. The taxon was found in a small soda spring which is an important water source for the Kızılırmak River. Surirella caljoniana is similar to Surirella brebissonii Krammer & Lange-Bertalot, S. brebissonii var. kuetzingii Krammer and Lange-Bertalot, S. lacrimula J.D.English, S. neglecta Reichardt and S. subsalsa W.Smith in morphology and shape. Unlike the other taxa, S. caljoniana has an oval-elliptic, slightly heteropolar outline, larger length/width ratio and a narrowly rounded, slightly protracted foot pole. Over the striae, distinct fimbriate silica protrusions are evident and similar to some marine species within the Pinnatae.